2016
DOI: 10.1089/jmf.2015.0148
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-Rich Blackcurrant Extract Attenuates Ovariectomy-Induced Bone Loss in Mice

Abstract: Although several animal and cell studies have indicated that blackcurrant anthocyanins exert antioxidative and anti-inflammatory properties, which could potentially improve bone mass, the effect of blackcurrant on bone health has not been reported yet. Thus, this study was aimed to evaluate the effect of blackcurrant anthocyanins on bone mass in an estrogen deficiency mouse model. Fourteen-week-old C57BL/6J mice (n = 54) were ovariectomized or sham operated. The ovariectomized mice were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
1
27
0
2
Order By: Relevance
“…The anthocyanin content of BC is composed of delphinidin (74% of total anthocyanins) and cyanidin (26%) [ 15 ], and delphinidin has been found to prevent bone resorption [ 16 ]. Animal studies [ 17 , 18 , 19 ] have demonstrated that certain fruits rich in anthocyanins improve bone mass. However, these studies utilized an ovariectomy (OVX)-induced osteoporosis model, which mimics postmenopausal estrogen deficiency but does not specifically mimic the effects of aging.…”
Section: Introductionmentioning
confidence: 99%
“…The anthocyanin content of BC is composed of delphinidin (74% of total anthocyanins) and cyanidin (26%) [ 15 ], and delphinidin has been found to prevent bone resorption [ 16 ]. Animal studies [ 17 , 18 , 19 ] have demonstrated that certain fruits rich in anthocyanins improve bone mass. However, these studies utilized an ovariectomy (OVX)-induced osteoporosis model, which mimics postmenopausal estrogen deficiency but does not specifically mimic the effects of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they identified that the supplement treatment down-regulated Ovx-induced elevation of alkaline phosphatase, collagen and tartrate-resistant acid phosphatase (TRAP) gene expression, suggesting that the bone-protective effect of blueberries may be due to the suppression of bone turnover (51). More recently, Zheng et al (52) identified that Ovx mice (14 weeks old) given a diet containing 1% anthocyanin-rich blackcurrant extract for 12 weeks had significantly greater femur BMD compared with Ovx control mice. Notably, they demonstrated that the extract reduced the number of TRAP-positive osteoclast-like cells and bone resorption activity, and concluded that the extract may alleviate bone loss by suppressing osteoclastogenesis and osteoclast function.…”
Section: Discussionmentioning
confidence: 99%
“…These other studies suggested that the effects of berry fruits or their extract on bone metabolism were more likely to be exerted through the suppression of bone resorption. Although previous in vivo studies (51,52) used mature Ovx rats, the rats used in the study by Zhang et al (56) were young Ovx rats in pre-pubertal growth stage. The ages of rats and the time after Ovx are important factors that may influence bone response following Ovx (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that blackcurrant anthocyanins exhibit a range of health benefits, including antioxidant [ 48 , 49 ] and anti-inflammatory effects [ 50 , 51 ], which could potentially improve bone remodeling. Several studies have utilized ovariectomized (OVX) animals to mimic the estrogen deficiency of menopause, and have found that supplementation with blueberry or blackcurrant attenuated the OVX-induced bone loss ( Table 3 ) [ 52 , 53 , 54 ].…”
Section: Antioxidant Intake and Bone Health: Potential Benefits Ofmentioning
confidence: 99%